A clinical trial of single dose rectal and oral administration of diazepam for the prevention of serial seizures in adult epileptic patients. Issue 3 (March 1984) - Milligan, N M; Dhillon, S; Griffiths, A; Oxley, J; Richens, A
Abstract : The clinical anticonvulsant efficacy of single dose rectal and oral administration of diazepam 20 mg was examined in two double-blind placebo-controlled trials in adult epileptic patients. All subjects suffered from drug resistant epilepsy and frequently experienced serial seizures. Diazepam was administered rectally as a new experimental suppository formulation immediately after a seizure and was highly effective in preventing recurrent fits within a 24 h observation period (p less than 0.001). Pharmacokinetic studies revealed a wide range of serum diazepam concentrations 60 min after administration of the suppository (mean serum diazepam level 190 +/- 73 (SD ng/ml). In a similar study oral administration of diazepam 20 mg significantly reduced the incidence of serial seizures compared with a placebo (p less than 0.01) and the mean 60 min serum diazepam level was 273 +/- 190 (SD) ng/ml.